The competitiveness of the state in the context of developing an innovative model for the world economic system (Путеводитель предпринимателя, 2020)
This article investigates the issues affecting the current and complex problem of international competitiveness of countries with a functioning economic system, based on innovations. The author has analyzed existing strengths in this area, by both domestic and foreign scientists and based on the information has clarified the definition of innovative competitiveness of the country, whose distinctive quality is its emphasis on the synergistic effects obtained from the integration of innovation and competitive advantage of the state. Special attention is paid to the innovative potential, which should be read in a dialectical unity of the country's competitive factors of innovation that will yield the greatest effect. The formation of leverage innovation capacity and its components are indicated. Based on the identified problems inherent in the development of innovative way, the recommendations aimed at increasing the level of innovativeness of the country are developed and as a consequence, of its level of competitiveness on a global scale.